POLIGAMI DAN PELAKOR, REFLEKSI DALAM FILM DAN REALITAS MASYARAKAT GORONTALO: SEBUAH STUDI PERBANDINGAN - La Ode Gusman Nasiru; Salam Salam; Eka Sartika (Jurnal Bahasa, Sastra, dan Budaya, 2023)
Nowadays, the issue of polygamy and homewrecker was an idea. It was found in two platforms such as the soap operas Suara Hati Istri and social reality in real life. Communal Gorontalo was the best prototype regarding these two issues. The motives, either polygamy or homewrecker in operas and in reality, were different. Soap operas put forward the basic trend and modernism as the basis, while the real life of the Gorontalo community proposed religion and legal awareness in its dynamics. Looking for the most fundamental thing connecting the two areas, the author used feminism theory as a comparative study. This study asked three questions such as (1) how was the reflection of polygamy and homewrecker in the Suara Hati Istri serial?; (2) what was the reflection of polygamy and homewrecker in the reality of Gorontalo society?; (3) what were the ideological concepts of polygamy and homewrecker in the series of Suara Hati Istri and in the reality of the Gorontalo community? Feminism succeeded found the fundamental reason for the similarities in the plurality of motives between soap operas and reality. It was toxic masculinity and misogynist.